Investigating the Association Between Internet Health Information Use and Patient Willingness to Communicate with Health Care Providers. Issue 6 (11th May 2020) - Baker, Susan C.; Watson, Bernadette M.
ABSTRACT: Communication between health professionals and patients is an intergroup phenomenon where the health professional has the most power and status. Over the past few decades, there has been a steady increase in the availability to patients of information about healthcare and specific diseases on the Internet. In this paper, we ask whether the use of Internet health information assists patients to manage their consultations with health professionals better and whether it alters the intergroup dynamic by providing a more equal status for patients. In this study 370 participants from Australia and Canada completed a survey that included a 'willingness to communicate with health professionals' scale. They also commented on their use and trust of Internet health information. Thematic analysis suggests that patients' use of Internet health information serves as a broker between patients and their health provider in health consultations. We discuss the implications of these findings for health practitioners as they address how easier Internet access influences patient interactions with health professionals. We consider future research directions these finding provide in explaining communication behaviour in this context.